Diikili Sebagai Ekspresi Islam Nusantara dalam Budaya Islam Lokal Gorontalo : Perspektif Dakwah Islamiyah - Erwin Jusuf Thaib (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2016)
Preaching has been deployed with a variety of media and approaches used. One medium of propaganda that is often used is culture. This phenomenon can be found in the majority culture of Gorontalo people embraced Islam. Melting the boundaries between religion and culture is a common thing for people of Gorontalo. Dikili is seen as one of the expressions of Islam Nusantara in Islamic culture of Gorontalo. Moral messages contained in the narrative Kitabi Lo Dikili relevant to preaching in general involves two aspects, aspects of the teachings of monotheism and moral teaching aspect / character of the Prophet Muhammad. Both of these aspects stand as it relates to the social setting that is faced by the Prophet when preaching for the first time in the city of Mecca.